Humanizing mathematics learning: secondary students beliefs on mathematics teachers' teaching efficacy - Ahmad Tarmizi, Mohd Ariff; Ahmad Tarmizi, Rohani; Mokhtar, Mohd Zin (Elsevier, 2010)
The importance of teaching mathematics as an integrated subject is recognized everywhere, not withstanding in Malaysia. Educating the pupils mathematically is more difficult, challenging and complex than teaching them some mathematics. In most of the countries including Malaysia the mathematical culture adapted in schools has the following characteristics viz. curriculum of procedures, methods, skills, rules and algorithms which insist on ‘doing’ mathematics rather than ‘thinking’ mathematics. Issues such as quantum of mathematics content, completion of stipulated syllabus in the given rigid time, examinations, interests and cognitive level of the learners were not given due considerations. Teachers generalize the learners ability i.e., teacher plans the lesson, teaches the lesson aiming at the average generalized ability of the learner considering it as every student's ability. It is evident that Mathematics teaching is dominated by dehumanisation, depersonalisation and decontextualisation. Students many times confused why are they learning about algebra, trigonometry theoretical proofs of theorems. Teaching mathematics in school classrooms is not contextual hence the aims of mathematically inclined learners are not realized by the students. The purpose of this study is to investigate the extent of humanizing mathematics among secondary mathematics teachers based on student's perception of their teachers’ practices in the classroom, specifically their beliefs about the classroom context such as the role and functioning of the mathematics teacher in the classroom. The mean scores for students’ beliefs in their teachers’ role and functioning in the mathematics classroom were positive with high ratings on showing step-by-step procedures in solving mathematical problems. Students also showed positive beliefs on teachers’ role in making mathematics learning enjoyable, interesting, and making learning mathematics understandable, meaningful and a friendly atmosphere.